(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Intelligent agro is now a growing concept that accentuates employment of ICT inside cyber-physical farmland managerial chain. The said growth is projected to be accelerated by newer advancements such as the Internet of Thing (IoT) & Mobile computing, which will enable ranchers to deploy increased machines with machine intelligence. All of that is represented by the Data Analysis phenomenon that alludes to massive volumes of data of different forms that may be gathered, processed, and used to make decisions. One purpose of current research is to get a better knowledge of the present state of Big Data processing in Precision Agriculture and even to uncover underlying accompanying psychosocial challenges that need to be addressed. A systematic technique has been used to construct a philosophical paradigm for assessment, which is often used in subsequent study on the issue. With regards to basic productivity, our research found that Data Analysis implementations in Agriculture 5.0 have an influence on this kind of agriculture distribution network. In farming activities, information systems is increasingly getting used to provide actionable analytics, dictate genuine logistical decisions, and reimagine workflows in way to build game-changing marketing strategies. As a consequence, many authors anticipate that Big Data will cause substantial alterations in the responsibilities & economic dynamics between different parties in current food distribution system ecosystems. The partner panorama exhibits a fascinating interaction involving giant virtual enterprises, venturing capitalists, &, on occasion, little entrepreneurs as well as entrants. Most municipal institutions, make accessible data available on the provision provided customers’ confidentiality be respected. From a sociological aspect, the authors suggest concentrating research on management policies including such accountability and acceptable business strategies for information exchange in diverse distribution network settings.